1996
DOI: 10.1095/biolreprod54.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Injecting Calcium Chloride into in Vitro-Matured Porcine Oocytes1

Abstract: In vitro-matured porcine oocytes were given injections of 0.1 M CaCl2 and after 6 h evaluated for signs of early and late activation events. CaCl2 injection caused cortical granule exocytosis in 75% (3 of 4) of the oocytes tested. It also induced cell cycle resumption as monitored by the histone H1 kinase assay: the phosphorylation rate of histone H1 decreased to 36.7% of the original value. Treated oocytes completed meiosis, extruded the second polar body, and progressed to first interphase: 79.4% of them for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…The release of cortical granules is induced by the increased [Ca 2+ ] i caused by the spermatozoon. It is also induced by different treatments, such as electro-stimulation [7] and microinjection of Ca 2 + [9,10] in the pig, calcium ionophore in the hamster [1], and exposure to the medium containing Sr 2+ in the mouse [36]. In the present study, cortical granules were released within 6-8 h after electro-stimulation or microinjection of sperm extract, and the result was consistent with the previous report [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The release of cortical granules is induced by the increased [Ca 2+ ] i caused by the spermatozoon. It is also induced by different treatments, such as electro-stimulation [7] and microinjection of Ca 2 + [9,10] in the pig, calcium ionophore in the hamster [1], and exposure to the medium containing Sr 2+ in the mouse [36]. In the present study, cortical granules were released within 6-8 h after electro-stimulation or microinjection of sperm extract, and the result was consistent with the previous report [11].…”
Section: Discussionsupporting
confidence: 92%
“…In the pig, an electro-stimulation technique [5] has been used for oocyte activation [6][7][8]. [9,10] and soluble sperm extract [11]. In many species studied so far, such as the hamster [12], mouse [13], human [14], cow [15] and pig [11], injection of sperm extract activates oocytes with repetitive increases in intracellular Ca Moreover, it has been reported that oocytes injected with sperm extract develop to blastocysts in the mouse [16], cow [16] and pig [11].…”
Section: Introductionmentioning
confidence: 99%
“…The sperm penetration is followed by the exocytosis of cortical granules within 6 hours (Yoshida et al, 1993). After parthenogenetic activation, the exocytosis of cortical granules was weaker than after the sperm penetration (Wang et al, 1998b), but many types of artificial activating stimuli are able to induce the exocytosis of cortical granules (Sun et al, 1992;Machatý et al, 1996Machatý et al, , 1997Okada et al, 2003). Cortical granule exocytosis followed very quickly after the activating stimulus .…”
Section: Does Nitric Oxide Activate Mammalian Oocytes?mentioning
confidence: 99%
“…On the other hand, we found that microinjection decreased MPF activity in NT embryos. This effect of microinjection seems not to be a result of aging during handling mentioned as above, but rather the influx of Ca 2þ ions (Machaty et al 1996). The influx of Ca 2þ ions involved in microinjection could be avoided by performing manipulation in the Ca 2þ ion-free medium; however, maintenance of porcine oocytes in a nondegenerated state requires the presence of Ca 2þ ions in the medium (Bae & Channing 1985).…”
Section: Mpf Activity In Porcine Nt Embryosmentioning
confidence: 99%